Partial Ceramic Veneer Technique for Challenging Esthetic Frontal Restorative Procedures - Gustavo Marotto Caetano; Cilea Slomp; Jonas Pereira Andrade; Ana Maria Spohr; Marcel Ferreira Kunrath (MDPI AG, 2023)
Frontal darkened teeth have shown to be one of the most challenging treatments for esthetic dentistry in recent years. This case report, along with a 30-month follow-up, describes the application of a partial ceramic veneer, restricted to the mid-cervical third region, made in the upper left central incisor darkened by trauma. The procedure consisted of maintenance of the entire incisal face, as well as esthetic and morphological rehabilitation of the smile line with veneers and ultra-thin partial ceramic veneers. The planning process was thoroughly elaborated by photographs, study models, a virtual smile designed, diagnostic waxing, and reproduction in the patient's mouth through mock-up. Following, dental home bleaching, esthetic gingival contouring, and minimally invasive tooth preparation were performed. Two types of glass ceramics (lithium disilicate and feldspathic) were used in different regions due to the peculiar characteristics of resistance, finishing, and polishing. According to the present case report, preparing a cervical partial ceramic veneer is an innovative, viable, and safe approach to maintaining the incisal portion of the tooth preserved and setting a detailed tooth morphology/color. The application of partial ceramic veneer provides incisal edge preservation and simplifies the reproduction of the adjacent tooth characteristics, avoiding multiple esthetic appointments.